Análise da influência de parâmetros adimensionais no modelo matemático de um reator tubular com perfil plano de velocidade - Berto, Carlos André Moreira Dal (2023)
Tubular reactors (PFR), commonly used in the industry for gas-phase reactions, can also be utilized for liquid-phase processes. To ensure effective application, proper sizing of the reactor is necessary, along with validation of the operating parameters for the intended purpose. One way to test its performance is through process simulation, which involves analyzing mass and energy balances to understand the stimuli occurring within the reactor. The objective of this work is to develop dimensionless mass and energy balances and to analyze the effect of varying their parameters on the behavior of the reactor. These balances were developed considering transient regime, piston flow, isobaric system, reversible liquid-phase reaction, constant physical properties. By obtaining its PDE (Partial Differential Equation), the reactor was dimensionless, summarizing the analysis into six parameters. The equation was solved using the method of lines, implemented in Python to generate the corresponding graphs. For each generated graph, information on the dimensionless concentration and dimensionless time was collected. The first parameter, 1 Pe i, demonstrated that the conversion of reactants to products is higher when the diffusion magnitude is greater than the product of the velocity and length. P2 indicated that as the reaction rate increases, the formation of products also increases until reaching equilibrium. P3 revealed that higher enthalpy of reaction leads to increased product formation, but there is also a significant temperature rise. P4 showed that there is an operating region where the process remains stable; if the values deviate too much from the optimal region, the reversibility of the reaction becomes evident with the formation of reactants instead of products. P5 indicated that thermal exchange with the environment benefits the process, but once it reaches a maximum value, the exchange ceases. P6 suggested that very low activation energy values can favor the process, as there is a higher organization of molecules.